2017
DOI: 10.1111/jocn.13827
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of health and self‐care among older persons—To be implemented in an interactive information and communication technology‐platform

Abstract: Areas relevant to older persons' health and self-care could be used for regular assessment to support and promote healthy ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Furthermore, the app includes a risk assessment model, so that alerts are sent to healthcare professionals for rapid management. The content developed for the current version is based on a literature review, and interviews with older people, nursing assistants and healthcare experts in order to identify the areas relevant to older people's health and self‐care (Göransson, Wengström, Ziegert, Langius‐Eklöf, Eriksson, Kihlgren & Blomberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the app includes a risk assessment model, so that alerts are sent to healthcare professionals for rapid management. The content developed for the current version is based on a literature review, and interviews with older people, nursing assistants and healthcare experts in order to identify the areas relevant to older people's health and self‐care (Göransson, Wengström, Ziegert, Langius‐Eklöf, Eriksson, Kihlgren & Blomberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Continuity and competence could, therefore, be important aspects to consider in order to meet the needs of older persons living with long-term health problems in the healthcare system. Göransson et al (2017) found that relationships and social activities are valuable for older persons' perceived health. To increase interaction with the surrounding society, information technology (IT) was found to be used by the older persons in the study; this appears to provide a new meaning in life for those with long-term health problems.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that health and welfare technology can support a healthy and independent life, social relations and meet individual needs of older people (Eisma et al, 2004;Magnusson et al, 2005;Koch, 2006;European Union, 2013Lee and Coughlin, 2014;Peek et al, 2014Peek et al, , 2016. Göransson et al (2017) concluded that it was essential to include social relationships and social activities in interactive information and communication technology (ICT) platforms aimed at older people. These findings, together with the findings from the current study, in which the importance of a social life also was reflected in the prerequisite of having access to health and welfare technology that facilitates/enables communication and social contacts (#34; 88%), indicates that the social aspects are relevant to older people's motivation to use ICT and should be integrated in interactive ICT platforms.…”
Section: Discussionmentioning
confidence: 99%